THE PROBLEM OF SOCIAL DETERMINATS OF MODERN PERSON’S REALIZATION IN POPE JOHN PAUL II’S PHILOSOPHICALTHEOLOGICAL TEACHING - Кохановська, М. Г. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
In the teaching of Pope John Paul II the main spheres of social life as determinants person’s realization in modern word are analysed.